The Effects of Diet, Physical Activity and Social Factors on Stress Perceived by Students - Daiva Vizbaraitė; Raminta Morkūnaitė (Lithuanian Sports University, 2018)
Backgroud. General health status of students is becoming worse due to an intensive lifestyle: a difficult job or study routine, improper diet, and low physical activity (Poteliūnienė, 2010). One of the common problems among students  is  stress.  Stressful  situations  on  a  daily  basis  have  been  found  to  be  associated  with  a  worse  physical and psychological status, harmful habits or personal relationships with friends (Dusselier, Dunn, Wang, Shelley, & Whalen, 2005; Leppink, Odlaug, Lust, Christenson, & Grant, 2016). Methods. According to the following questionnaires, dietary habits and some social peculiarities (Grabauskas, Zaborskis,  Klumbienė,  Petkevičienė,  &  Žemaitienė,  2004),  physical  activity  (Aadahl  &  JØrgensen,  2003)  and perceived stress (Konduri, Gupchup, Borrego, & Worley-Louis, 2006) by female and male students were determined. The data obtained were processed using mathematical statistical methods. The relationships between qualitative determinants were evaluated by chi square (χ 2 ) criterion. A value at p < .05 was considered significant. Statistical analysis  was  performed  using  SPSS  (version  17.0)  (Statistical  Package  for  Social  Science  17.0  for  Windows) statistical software package. Results. Male students (54.2%) who were following a dietary regime reported experiencing low level of stress, and those students (45.2%) who were not having a dietary regime perceived moderate level of stress. Married female students (80%) responded that they experienced low level of stress, moderate level of stress was indicated by 72.7% of females living with a partner and 40% of females who had a boyfriend, and 38.5% of single females reported having high level of stress. Conclusions. Male students who were following a dietary regimen reported experiencing lower level of stress, and those students who were not having a dietary regimen responded that they perceived moderate level of stress. A dietary regimen and perceived stress did not differ among female students. Different levels of physical activity were not associated with stress experienced by female and male students (p > .05). Married female students did not perceive high level of stress; moderate level was reported by females living with a partner; high level of stress - by single students. Marital status and perceived stress did not differ in male students. Keywords:  physical activity, diet, social factors, stress.